Формування педагогічної культури батьків як основа взаємодії дошкільного навчального закладу та сім’ї - Семенова, Наталія Іванівна; Сільчук, Анна; Semenova, Nataliia I.; Silchuk, Anna (Прикарпатський національний університет імені Василя Стефаника, 2016)
У статті розглянуто проблему формування педагогічної культури батьків як основу взаємодії дошкільного навчального закладу та сім’ї. Проаналізовано останні дослідження, у яких започатковано розв’язання цієї проблеми. Розкрито сутність поняття педагогічна культура батьків. In the article the problem of formation of pedagogical culture of parents as the basis for interaction between kindergarten and family. Analyzed past studies in which a solution of the problem. The essence of the concept of pedagogical culture of parents. Identified the basic functions of the family. The characteristic principles of individual and group forms of cooperation between kindergarten and family.
Formation of pedagogical culture of parents as the basis of interaction pre-school and family
Keywords: взаємодія; педагогічна культура батьків; дошкільний навчальний заклад; формування; interaction; pedagogical culture of parents; pre-school institution; formation